The Effect of Educational Intervention based on Social Support Theory on Improvement of Hemodialysis Patients' Quality of Life - Leila Zhianfar; Mahnaz Solhi; Farbod Ebadi Fard Azar; Agha Fatemeh Hosseini; Seyed Fahim Irandoost (Iranian Journal of Health, Safety and Environment, 2021)
Chronic kidney failure is a progressive and irreversible degeneration of renal function that affects the quality of life of patients. Social support as a coping mechanism can help promote health and improve the quality of life of a person. The purpose of this study was to determine the effect of educational intervention based on social support theory on the improvement of hemodialysis patients' QOL. This is a controlled quasi-experimental conducted in 2015 in Sari and with the participation of 100 hemodialysis patients that were randomly assigned to 2 groups. Prior to education, the patients were evaluated with demographic form, quality of life (WHOQOL-BREF) and social support (MOS-SSS) questionnaires. Then, an educational program was developed based on social support theory and implemented for the intervention group. The two groups were re-evaluated with the same questionnaires after 1 and 3 months and the data were analyzed in SPSS. In the intervention group compared to the control group, the mean scores of quality of life and social support increased significantly after the intervention (p